Irisin, Exercise, and COVID-19 - Alves, Hugo Rodrigues; Lomba, Guilherme Schittine Bezerra; Gonçalves-de-Albuquerque, Cassiano Felippe; Burth, Patricia (Frontiers in Endocrinology, 2022)
Muscle and adipose tissue produce irisin during exercise. Irisin is thermogenic adipomyokine, improves glucose and lipid metabolism, and ameliorates the effects of obesity-driven inflammation, metabolic syndrome, and diabetes. In addition, exercise-induced irisin activates anti-inflammatory pathways and may play an essential role in improving the outcomes of inflammatory conditions, such as coronavirus disease (COVID-19). COVID-19 infection can activate different intracellular receptors and modulate various pathways during the course of the disease. The cytokine release storm (CRS) produced is significant because it promotes the context for systemic inflammation, which increases the risk of mortality in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). In addition, viral infection and the resulting organ damage may stimulate the mitogen-activated protein kinase(MAPK) and toll-like receptor 4 (TLR4)/toll interleukin receptor (TIR)-domain-containing adaptor (MyD88) pathways while negatively modulating the AMP-activated protein kinase (AMPK) pathway, leading to increased inflammatory cytokine production. Exercise-induced irisin may counteract this inflammatory modulation by decreasing cytokine production. Consequently, increased irisin levels, as found in healthy patients, may favor a better prognosis in patients with SARS-CoV2. This review aims to explore the molecular mechanisms underlying the anti-inflammatory properties of irisin in mitigating CRS and preventing severe outcomes due to infection with SARS-CoV2.